(untitled) (Research, Society and Development, 2021)
Introduction: The SARS-CoV-2 pandemic had an impact on sexual and reproductive health mainly because it is a disease with high transmissibility among individuals in close contact. Objective: Assess the impact of social isolation on sexual function, quality of life, and self-image of nulliparous women, before and during the SARS-CoV-2 pandemic. Methods: Longitudinal observational analytical study, with women aged 18 to 35 years, nulliparous, with complete high school education, who had not undergone previous physical therapy treatment. The data collection included anthroposociodemographic data and the Female Sexual Function Index (FSFI), Short Form Health Survey 36 (SF-36) questionnaires, and the Stunkard, Sorensen and Schlusinger Silhouettes Scale (self-image assessment), applied before and during social isolation. Statistical analysis was performed on GraphPad Prisma 6.0, and the Shapiro Wilk test was used to analyze the sample distribution, which was nonparametric, then the Wilcoxon test and Spearman’s correlation were applied. The level of significance adopted was p≤0.05. Results: 37 volunteers were evaluated, the sociodemographic variables and the body mass index showed no difference between the evaluations, during social isolation the number of sedentary women increased (p <0.0001), the orgastic function improved (p = 0.0081), the pain worsened significantly in SF-36 (<0.0001), and the better the General Health Status of SF36, the better the sexual function [p = 0.04; r = 0.37], in the correlation of physical activity, the type of social isolation and the total score obtained in the FSFI questionnaire, no significant correlations were found. Conclusion: Social isolation favored the improvement of orgastic function, the worsening of pain in the SF-36, and did not interfere with the dissatisfaction of body image, which remained similar.